DAMPAK DIMENSI EXPERIENTIAL MARKETING TERHADAP KEPUASAN KONSUMEN, TIMBULNYA WORD OF MOUTH DAN MINAT BELI ULANG (Studi Kasus Jasa Pencucian Kendaraan Maxx Carwash & Detailing Semarang) - Naufaldy, Iqbal; Sukresna, I Made (Diponegoro Journal of Management, 2017)
Maxx Carwash & Detailing is one of the premium carwash in Semarang. In the last two years, Maxx Carwash & Detailing began to experience symptoms of decline. Customer dissatisfaction of services and facilities is the reasons why people stop using a company’s service. Thus, the company needs to be able to implement strategies in order to keep or increase consumer interest in using services offered by Maxx Carwash & Detailing.Maxx Carwash & Detailing has a problem on the number of services that dropped significantly on two treatments offered. For car wash service during the period 2015 to 2016 there was a decrease in the number of services by 11.52%. As for the service doorsmeer decreased the amount of service amounted to 48.79%. In addition, in the pre-survey conducted, researchers also found some complaints from consumers, namely the most are a long service time and waiting room that is less comfortable..This study aims to analyze the effects arising from sense experience, feel experience, think experience, act experience towards customer satisfaction and word of mouth in increasing customers’ intentions to repurchase Maxx Carwash & Detailing’s services. The method used in collecting data is insidental sampling. This study has 165 samples that were collected through questionnaires. Questionnaires were distributed to the respondents who have ever tried using Maxx Carwash & Detailing’s services in Semarang. The data   collected were processed using Structural Equation Modeling (SEM) through AMOS ver. 23.0 by testing seven hypotheses.Based on the research of data processing SEM for full model has met the criteria of goodness of fit as follows, the value of chi-square = 279,286; probability = 0,222; RMSEA = 0,020;  CMIN/DF = 1,066; TLI = 0,986; CFI = 0.988, and two marginal criteria which are GFI = 0,886 and AGFI = 0,859. With the result, it can be said that this model is feasible to be used. The result showed that sense experience through customer satisfaction and word of mouth has the most significant impact on repurchase intention. Thus, in order to increase repurchase intention, Maxx Carwash & Detailing needs to increase sense experience and customer satisfaction.